Radioembolization treatment for liver metastases - Kiszka, Joanna; Karczmarek-Borowska, Bożenna (Contemporary Oncology/Współczesna Onkologia, 2017)
The liver is an organ that, due to vascularisation and functions, is prone to metastases. Most liver metastases are observed in cases of gastrointestinal cancers in: stomach, colon, gallbladder, and bile ducts. Metastatic lesions are also observed in lung, breast, thyroid, kidney, and pancreatic cancer. One of the best known and most effective ways of liver lesion treatment is Metastasectomy. Unfortunately, lesions are frequently inoperable. Apart from chemotherapy, it is possible to apply local treatment such as TACE (trans-arterial chemoembolisation), RFA (Radio Frequency Ablation), and SBRT (Stereotactic Body Radiation Therapy). One of the newest methods of inoperable lesion treatment is radioembolisation (SIRT). Intravascular administration of microspheres containing radioisotope 90Y allows delivery of a higher dose of radiation directly to the tumour than traditional radiation with an external beam, while maintaining a small dose to healthy liver methods. Conducted clinical studies confirm the efficacy and safety of SIRT. It is an interesting alternative to other ways of treatment.